(untitled) - ROSANDI, SHINDA (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Competition in business either liquid milk drink milk or milk powder tighter due to increased activity of the population.. One of the dairy beverage products that success in the market is Ultra Milk. In an effort to maintain the continuity of its business, in August 2013, Ultra Milk creates innovations of the latest packaging that is environmentally friendly tetra pack packaging. By utilizing the brand image of the Ultra Milk as beverage milk quality and contain all the essential nutrients for the body and supported by an attractive packaging design, is expected to be able to attract consumers. This study aims to analyze and discuss the influence of brand image and packaging design to consumer buying interest at Ultra Milk products. This type of research is quantitative. The technique of sampling using accidental sampling with a sample of 356 respondents, as well as using multiple linear regression analysis with the help of software SPSS 16.0 for Windows. The results shows that the image of the brand and design packaging significantly influence consumer buying interest, which is the brand image of the dominant variable affecting. This is because Ultra Milk brand s has been known in Indonesia and has a quality that is able to make it stand out compared to its competitors. While the packaging design becomes less variable role in shaping buying interest. Keywords: brand image, packaging design, buying interest